Sistem Kontrol dan Pengamanan Kotak Penyimpanan Uang Menggunakan Aplikasi Telegram Berbasis Arduino - Fahmy Anugrah (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
In the digital technology era, the traditional method of saving money through piggy banks is becoming less popular. A new innovation in the form of a microcontroller-based money storage box has replaced the traditional saving method. This box is connected to smartphones via the Telegram Bot application and equipped with GPS technology for location tracking. With password protection, this box ensures security and provides balance information. Utilizing the NodeMCU ESP8266 as a microcontroller and the TCS3200 sensor to detect currency colours, the box also employs the GPS Neo 6m for precise location tracking using Google Maps. Through testing, the box is capable of distinguishing currency types, providing accurate balances, and conducting tracking via Google Maps. Operating without external power sources, this box offers an efficient and secure solution for saving money, featuring control through smartphones, accurate tracking, and high security.